2019
DOI: 10.3390/ma12234016
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Demolition Waste as Recycled Aggregates in Alkali-Activated Concretes

Abstract: The growth of global construction has contributed to an inevitable increase in the amount of construction and demolition (C&D) waste, and the recycling of C&D waste as aggregates in concrete is receiving increased interest, resulting in less demand for normal aggregates and bringing a potential solution for the landfilling of wastes. Recently, several studies have focused on the use of C&D waste in alkali-activated concrete to move one step closer to sustainable concretes. This paper focuses on the main mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 110 publications
0
16
0
Order By: Relevance
“…A recent work by Galetakis and Soultana [15] reviewed the use of quarry fines in the preparation of building materials. Authors found that slurries can be used as fine aggregates or as cement replacement [25][26][27], while solid waste can, in part, substitute aggregates in concrete mixtures, as already proposed in literature for other wastes as well [28][29][30][31][32]. More recently, the possibility of including fine quarry wastes into new alkali-activated products has been investigated, similarly to what other researchers are doing as regards alkali-activated materials containing mine tailings (i.e., the finely ground residue from ore extraction) [33][34][35][36].…”
Section: Introductionmentioning
confidence: 95%
“…A recent work by Galetakis and Soultana [15] reviewed the use of quarry fines in the preparation of building materials. Authors found that slurries can be used as fine aggregates or as cement replacement [25][26][27], while solid waste can, in part, substitute aggregates in concrete mixtures, as already proposed in literature for other wastes as well [28][29][30][31][32]. More recently, the possibility of including fine quarry wastes into new alkali-activated products has been investigated, similarly to what other researchers are doing as regards alkali-activated materials containing mine tailings (i.e., the finely ground residue from ore extraction) [33][34][35][36].…”
Section: Introductionmentioning
confidence: 95%
“…The Portland cement can be then completely replaced by AAMs in order to mix concrete [3,4]. Besides, some glass waste [5], construction and demolition waste [4,6] can be recycled as fine and coarse aggregates instead of natural aggregates. Eco-friendly green concrete is consequently obtained [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some glass waste [5], construction and demolition waste [4,6] can be recycled as fine and coarse aggregates instead of natural aggregates. Eco-friendly green concrete is consequently obtained [4,5]. Moreover, it is well known that the ocean area is much larger than the mainland area on the earth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, due to the large water absorption and weak bond strength with new matrix, the mortar attached on the aggregates was another factor which degraded the quality of recycled aggregates [ 17 ]. Both the micro-porosity in cement paste and the mesoporosity between particles increase the water absorption of RCA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%